The case of Henryk Erlich and Victor Alter - Huysmans, Camille; General Jewish Workers' Union of Poland (London : Liberty Publications, 1943)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Erlich, Henryk; Alter, Victor; Wereldoorlog 2; Polen